2007
DOI: 10.3171/spi-07/12/587
|View full text |Cite
|
Sign up to set email alerts
|

Spinal dumbbell tumors: an analysis of a series of 118 cases

Abstract: Object The authors analyzed a series of 118 cases of spinal dumbbell tumors to elucidate the feature of the tumors. Methods Of 674 cases of spinal cord tumors, the incidence of dumbbell tumors was studied. The tumors were analyzed, and the authors focus on the distribution of age and sex, the pathological diagnoses, their locations, Eden classification, and the surgical methods used. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
111
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 205 publications
(121 citation statements)
references
References 9 publications
3
111
0
7
Order By: Relevance
“…There is no controversy about the surgical approach for the mere intraspinal or paravertebral tumor, which is classified as Eden type 1 or type 4 [4, 13]. This study focused on the surgical treatment for Eden types 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There is no controversy about the surgical approach for the mere intraspinal or paravertebral tumor, which is classified as Eden type 1 or type 4 [4, 13]. This study focused on the surgical treatment for Eden types 2 and 3.…”
Section: Discussionmentioning
confidence: 99%
“…This study focused on the surgical treatment for Eden types 2 and 3. There is still great controversy about the approach used for the removal of these 2 types of tumors [4, 9]. Jiang et al [8] classified the dumbbell tumors into 7 types on the basis of Eden’s classification and according to the tumor size in the external vertebra, whether tumor invades into the vertebra, the relationship between the location of the intraspinal tumor and the spine cord, and so on.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies of the population-based epidemiology of primary spinal cord tumors have been conducted in USA and Europe [3,4,5,6,7,8]. To our knowledge, there are no population-based studies in Asia including Japan, although many case series had been reported [9,10]. …”
Section: Introductionmentioning
confidence: 99%